If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 4 = 25 + 4w Reorder the terms: 4 + 2w = 25 + 4w Solving 4 + 2w = 25 + 4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4w' to each side of the equation. 4 + 2w + -4w = 25 + 4w + -4w Combine like terms: 2w + -4w = -2w 4 + -2w = 25 + 4w + -4w Combine like terms: 4w + -4w = 0 4 + -2w = 25 + 0 4 + -2w = 25 Add '-4' to each side of the equation. 4 + -4 + -2w = 25 + -4 Combine like terms: 4 + -4 = 0 0 + -2w = 25 + -4 -2w = 25 + -4 Combine like terms: 25 + -4 = 21 -2w = 21 Divide each side by '-2'. w = -10.5 Simplifying w = -10.5
| 14x=36 | | ln(x+1)-ln(x)=2 | | 7-2x=25 | | ln(-7x+5)=12.25 | | x+3x-34=180 | | 5x+18y=16 | | 12*31= | | 5x-15y=20 | | 4a+28= | | 2x-1*x*x+8*2x+5*x-3= | | X^2+16-8x=0 | | (2x+3)-(x+1)=(x+1) | | x+5*x-3= | | 9x-84=4x-14 | | 3(7t-14)=-21t+42 | | 2x+5*2x+5= | | 159-4x=32x+23 | | (2x-y)(4x^2-y^2)=a | | (4x+y)(8x^2-2y^2)=a | | 3.54=x+1.2 | | 12x+5-3x-3=6x-25 | | -6(v-2)=-4v+22 | | -9v-32=-2(v+9) | | -2(r+9)=-39 | | 2(v+5)=6v+14 | | 10=9x+4-6x | | 3x-9y=15 | | 7t+8(4-3t)= | | 4.7=6.7-0.4x | | 2x+4x-7=23 | | 9c=3 | | (9xy-2x^2)(2x+y)=a |